Analisis Semantik Pada Serat Amanat Galunggung: Para Penguasa Penerus Tahta Kerajaan Galuh - Siti Asiah; Nita Khairunnisa; Ai Fuadzah; Aveny Septi Astriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aims to reveal and analyze the fiber of Galunggung's mandate: The Successor Rulers to the Throne of the Galuh Kingdom. The research method used is a type of descriptive research analysis of the fiber of trust in Sundanese culture with the application of content analysis techniques carried out with systematic characteristics. Therefore, the researcher's focus is on studying the fiber of meaning that exists in Sundanese culture by using the concept of structural description to explain the types of meaning contained in poetry, starting from connotative meaning and denotative meaning. The results of this research reveal three mandates which are a form of advice to the next generation to always obey the adages of their parents in order to live a safe and prosperous life, then the next generation must also always guard their words when speaking, and the last is that every event has a cause and effect so that When behaving, there needs to be rules that lead to goodness so that the results you reap will be good.